Organizing Solidarity Initiatives: A Socio-spatial Conceptualization of Resistance - Daskalaki, Maria; Kokkinidis, George (My University, 2017)
This paper offers a spatial conceptualization of resistance by focusing on the practices through which solidarity initiatives constitute new resistance socio-spatialities. We discuss two solidarity initiatives in Greece, WCNA and Vio.Me.SI, and explore how they institute distinctive local and translocal organizational practices that make the production of new forms of resistance possible. In particular, we adopt a productive and transformative view of resistance. First, we identify three local practices of organizing solidarity initiatives, namely, the organization of general assembly meetings, the constitution of resistance laboratories and the (re)articulation of socio-spatial relations in local sites. Then, we turn to flows, movements and translocal social formations, and examine the role of solidarity mobilizations, the material and symbolic co-production of resources and members’ mobility in the production of resistance. We conclude that new resistance socio-spatialities become constitutive of a broader reconfiguration of political agencies, a creative process that challenges existing relations and invites alternative ways of working and organizing.
Keywords: mobilities; solidarity; resistance; socio-spatial relations; space; translocal